Survey on Patients' View of Pharmaceuticals in the Multiple Medical Institutions - TSUGITA, MASAMI; KAWASE, HIDEKAZU; ONO, KAZUKO; SUTOH, YOUKO; SASAHARA, MAYUMI; TOYAMA, KAZUMI; KAJIWARA, KENSUKE; UNO, KATSUJI; TOBITA, MIEKO; YOHKOH, NORIAKI; ABE, MANABU; NAGAI, KAZUHIKO; et al. (Byōin yakugaku, 1999)
A questionnaire survey of patinets' views regarding pharmaceuticals was carried on 4264 drugadministered patients more than 16 years of age at 13 medical institutions, consisting 9 hospitals and 4 pharmacies in the suburbs of Niigata City. The results were as follows: 1. The degree of patinet concern about pharmaceuticals was 33.7%(95% confidence interval 27.8-39.6). The score was significantly higher in young patients than in elderly patients (P<0.0001), in females than in males (P=0.0002), in inpatients than in outpatients (P< 0.0001) and in the 2 university hospitals than in the other 11 institutions (P< 0.0001). 2. Regarding the information which the patients wanted to know about the pharmaceuticals, 53.1 % wanted to know about the “effects of the drugs”, 44.7% about the “adverse effects of the drugs”, 27.2% about “drug interactions” and 21.2% about “name of drugs” . Therefore, a high percentage of patients wanted to know about both the “effects of the drugs” and the “adverse effects of the drugs” . 3. The degree of patient anxiety about any adverse effects of the drugs was 23.0%(95% confidence interval 19.7-26.3). This percentage was significantly higher in young patients than in aged patients (P< 0.0001), in females than in males (P<0.0001), in the 6 institutions providing no 300 drug information than in the 7 institutions providing drug information (P=0.0431) and in the 9hospitals than in the 4 pharmacies (P<0.0001).